Evaluation of Electrochemical Reduction of Chloroform by Drop Mercury Electrode - Hossein Arbab-Zavar, Mohammad; Hossein Rounaghi, Gholam; Chamsaz, Mahmood; Ashraf, Narges (Asian Journal of Chemistry, 2010)
In this work, the reduction wave of chloroform was studied by differential pulse polarography (DPP) and square wave voltammetry (SWV). The effects of supporting electrolyte and solvent were discussed. In DPP experiments, the reduction wave of chloroform was observable in aqueous solutions of tetramethylammonium bromide (TMABr) and tetraethylammonium bromide (TEABr) as the supporting electrolytes. Water, ethanol and dimethylsulfoxide (DMSO) were examined as solvents to find the most suitable solvent. Square wave voltammetry technique was chosen to study the quantitative parameters in different solvents. DMSO proved to be the best due to its sensitivity, reproducibility, limit of detection and strong interaction with chloroform. Cyclic voltammetry was employed in order to elucidate the electrode reaction mechanism. Bromoform was also studied and the differences between the electrode reaction mechanisms of chloroform and bromoform were distinguished.